Kinesthetic Intelligence Based Learning to Improve the Students Motivation and Learning Outcomes in Managing Corpses Based on the Islamic Law - Ahmad syaeful Rahman; Mohamad Athoillah (International Journal of Islamic Khazanah, 2022)
The low motivation of students can be caused by the monotony of learning activities. Besides that, teachers are less varied in delivering material because they always use conventional methods, so that students play a less active role in learning. The involvement of students in learning will create a good impression and, of course, can make learning more meaningful, especially if students are directly involved in observations and practical activities. One of the learning strategies that can be used to attract students' attention is multi- intelligence-based learning. Learning activities based on multiple intelligences that are appropriate to the characteristics of the Fiqih material regarding the management of corpses are kinesthetic intelligence. The subjects in this study involved students in grades IX B and IX C MTs. As-Sa'adah Sukasari totaled 36 and 37 students, respectively. The instruments used in this study include observation sheets, motivation and multiple intelligence questionnaires, and learning outcomes tests. The results showed that students' motivation and learning outcomes increased after learning based on multiple intelligences. This can be seen from the average category of multiple intelligence questionnaire results on kinesthetic intelligence indicators of 80.77 with very good criteria. The results of the motivation questionnaire in the experimental class after learning multiple intelligences in the experimental class have a very high category (84.57), while in the control class it has a medium category (55.57). Student learning outcomes in the experimental class increased in the medium category (N-Gain 0.53) while the learning outcomes in the control class were in the low category (N-Gain 0.12).